Design and performance of a bidirectional isolated DC-DC converter for a battery energy storage system - Tan N.M.L.; Abe T.; Akagi H. (2023)
This paper describes the design and performance of a 6-kW, full-bridge, bidirectional isolated dc-dc converter using a 20-kHz transformer for a 53.2-V, 2-kWh lithium-ion (Li-ion) battery energy storage system. The dc voltage at the high-voltage side is controlled from 305 to 355 V, as the battery voltage at the low-voltage side (LVS) varies from 50 to 59 V. The maximal efficiency of the dc-dc converter is measured to be 96.0 during battery charging, and 96.9 during battery discharging. Moreover, this paper analyzes the effect of unavoidable dc-bias currents on the magnetic-flux saturation of the transformer. Finally, it provides the dc-dc converter loss breakdown with more focus on the LVS converter. 2011 IEEE.